Revisiting Island Decolonization: The Pursuit of Self-Government in Pacific Island Polities Under US Hegemony - Moritz Pöllath (Island Studies Journal, 2018)
The final years of the Cold War and the following decade led to a short historical intermission in the United States’ strategic interest in the Pacific. During that period the Trust Territory of the Pacific was dissolved and three former districts gained their independence as the Republic of Marshall Islands, the Federated States of Micronesia, and the Republic of Palau. The Commonwealth of the Northern Mariana Islands, American Samoa, and Guam, which became unincorporated US territories, remain constitutionally linked to the United States and their political status unresolved. From the legal perspective of the United Nations only American Samoa and Guam are still considered non-self-governing territories and thereby covered by the Special Committee on Decolonization. The return of geopolitical competition to the Pacific due to the rise of China is reviving the question of self-determination in these island polities anew. At the same time, the intention remains to preserve the political and economic links with the United States, calling into question traditional concepts of decolonization. This study will analyze Pacific islanders’ current pursuit of self-government under US hegemony, in order to clarify whether or not these islands are still determined by the process of decolonization or are taking different paths.